The Oniad Sibyl: how a Greek prophetess became a revolutionary mouthpiece for Egyptian Jews - Vargas, Miguel M. (Studia in Veteris Testamenti pseudepigrapha, 2025)
"The Oniad community was a mercenary and priestly Jewish settlement in Greco-Roman Egypt. This community recognized an exiled high priest of the Jerusalem Temple as its founder and met its end after a Mediterranean-wide uprising that shook the foundations of the Roman Empire. This monograph attributes a group of rather puzzling prophetic narratives-filled with coded language, reused lines from Greek and Jewish literature, and confused historical references-to the Oniads. The thesis of this study is that each prophetic treatise responds to crises experienced by the Oniad settlement and, as a result, evidences its unfolding historical consciousness and hybrid literary culture in distinct phases of its existence"--